DENUDATION AND COOLING OF THE LAKE TELETSKOYE REGION IN THE ALTAI MOUNTAINS (SOUTH SIBERIA) AS REVEALED BY APATITE FISSION-TRACK THERMOCHRONOLOGY - Grave J.De.; Haute P.V.D. (My University, 2002)
Lake Teletskoye occupies a narrow graben located in the northwestern sector of the Altai fold belt in South Siberia. The lake basin is thought to have formed during the Pleistocene as a distant result of the Cenozoic collision of India and Eurasia that caused a tectonic reactivation of the Palaeozoic Gorny–Altai (GA) and West Sayan (WS) blocks.The present work reports of a pilot fission-track study performed on 13 apatite separates collected from rocks that were sampled along two profiles in close proximity of the lake. The age–length data and AFT thermochronological modelling reveal two important phases of cooling in the Altai Mountains, a first one during the Late Jurassic–Early Cretaceous and a second one that started in the Miocene–Pliocene and that persists until today. The first event is interpreted to result from uplift-induced denudation probably related to the closure of the Mongol–Okhotsk Ocean; the second event can be linked to the young Cenozoic movements that lie at the origin of the formation of the Lake Teletskoye basin.